Rejuvenation of the term sarcopenia - Bulow, J; Ulijaszek, S; Holm, L (American Physiological Society, 2018)
It is our viewpoint that the recent consensus definitions of sarcopenia are dysfunctional for clinical and experimental practice as well as in theory. In 1989, the term sarcopenia was introduced to describe the phenomenon of age-related loss of lean body mass (10). Since 2010, six consensus definitions have been presented, and in 2016, it was assigned its own ICD-10 code (1, 3, 5, 6, 8, 9, 11). A comparison of the original definition with the new consensus definitions clarifies how the term sarcopenia no longer describes the phenomenon it originally addressed. Rather, the term is now caught in tautological association, which causes confusion and hinders rather than helps understanding of this condition.